2018
DOI: 10.1186/s12859-018-2309-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting overlapping protein complexes based on core-attachment and a local modularity structure

Abstract: BackgroundIn recent decades, detecting protein complexes (PCs) from protein-protein interaction networks (PPINs) has been an active area of research. There are a large number of excellent graph clustering methods that work very well for identifying PCs. However, most of existing methods usually overlook the inherent core-attachment organization of PCs. Therefore, these methods have three major limitations we should concern. Firstly, many methods have ignored the importance of selecting seed, especially without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…We have experiments on six PPINs to compare our SE-DMTG algorithm with the following state-of-the-art protein complex detection algorithms, including MCODE [28 ], MCL [ 34 ], CFinder [ 26 ], DPClus [ 29 ], IPCA [ 30 ], CMC [ 27 ], COACH [ 32 ], HC-PIN [ 41 ], SPICi [ 31 ], ClusterONE [ 35 ], WPNCA [ 33 ], CALM [ 36 ], and ClusterEPs [ 43]. Here all parameters are set as their authors advised in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have experiments on six PPINs to compare our SE-DMTG algorithm with the following state-of-the-art protein complex detection algorithms, including MCODE [28 ], MCL [ 34 ], CFinder [ 26 ], DPClus [ 29 ], IPCA [ 30 ], CMC [ 27 ], COACH [ 32 ], HC-PIN [ 41 ], SPICi [ 31 ], ClusterONE [ 35 ], WPNCA [ 33 ], CALM [ 36 ], and ClusterEPs [ 43]. Here all parameters are set as their authors advised in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [30 , 35 , 36] have shown that the accuracy of protein complex detection can be significantly improved by taking network weights into account. In the following subsections, we introduce how to calculate the weight of the PPIN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results suggest that MLQCC + LI improves the performance of MLQCC on large-scale instances. In future work, we will continue to improve the effectiveness of our algorithms and design various heuristics (Brandão et al, 2017;Interian and Ribeiro, 2017;Wang et al, 2018a) to obtain a better solution quality. Also, we will try to use these proposed strategies in some other problems (Moraes et al, 2016;Wang et al, 2017a;Liu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, evolutionary algorithm [15, 16] has been adopted to avoid poor local minimum; and node embedding [17] have been used to transform the graph clustering problem into a conventional clustering problem. In addition, algorithms [18, 19] combining two or more approaches described above has emerged. Unfortunately, the computational methods for functional module identification are clearly limited by the poor quality of the underlying PPI data, which is noisy with high rates of false positive and false negative [20, 21].…”
Section: Introductionmentioning
confidence: 99%